2019
DOI: 10.3390/ceramics2030036
|View full text |Cite
|
Sign up to set email alerts
|

Towards In-Situ Electron Microscopy Studies of Flash Sintering

Abstract: Flash sintering, a special case of electric field-assisted sintering, results in accelerated densification at lower temperatures than conventional sintering methods. However, the mechanisms remain elusive despite the wide application potential. In-situ electron microscopy studies reveal shrinkage of ZnO green bodies due to both heating and heating/biasing but show no obvious effect of the current on the behavior. In contrast, thin epitaxial ZnO films deposited on an Al2O3 substrate undergo a clear flash event … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
(44 reference statements)
0
6
0
3
Order By: Relevance
“…In particular, in transmission electron microscopy (TEM), the introduction of Micro Electronic Mechanical System (MEMS) chip‐based holders has led to the rapid development of methodologies allowing to directly relate structure and composition with material functionality (Alam et al, 2020; Allard et al, 2009; Creemer et al, 2010; Gaulandris et al, 2020; Mele et al, 2016; Niekiel et al, 2017; Vijayan & Aindow, 2019; Yokosawa et al, 2012; Zheng et al, 2022; Zintler et al, 2017). MEMS chips are also employed in conjunction with scanning electron microscopy (SEM) for in‐situ and operando experiments (Mølhave et al, 2004; Schwarzbach et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, in transmission electron microscopy (TEM), the introduction of Micro Electronic Mechanical System (MEMS) chip‐based holders has led to the rapid development of methodologies allowing to directly relate structure and composition with material functionality (Alam et al, 2020; Allard et al, 2009; Creemer et al, 2010; Gaulandris et al, 2020; Mele et al, 2016; Niekiel et al, 2017; Vijayan & Aindow, 2019; Yokosawa et al, 2012; Zheng et al, 2022; Zintler et al, 2017). MEMS chips are also employed in conjunction with scanning electron microscopy (SEM) for in‐situ and operando experiments (Mølhave et al, 2004; Schwarzbach et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Such experiments have given insight into, for example, solid state battery dynamics (Basak et al, 2022; Hammad Fawey et al, 2016; Wang et al, 2020; Yang et al, 2016; Zhang et al, 2022). With the use of combined heating‐biasing holders, such measurements can be performed as a function of temperature (Schwarzbach et al, 2019). In a recent study, we showed that by combining the heating‐biasing chips with an environmental TEM (ETEM) it is possible to perform reliable electrochemical impedance spectroscopy (EIS) measurements of solid oxide cell components in the TEM (Ma et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…One option is the processing of metals with magnetic and electric fields, which offers new possibilities for synthesis and control of microstructures. [ 1–6 ]…”
Section: Introductionmentioning
confidence: 99%
“…One option is the processing of metals with magnetic and electric fields, which offers new possibilities for synthesis and control of microstructures. [1][2][3][4][5][6] Electric fields, and the resultant currents produced in metals, have long been known to lead to directed atom transport or electromigration. [7,8] Electromigration has been a serious reliability issue for integrated circuits over the years because it can eventually result in the formation of voids and hillocks and lead to failure of conductor lines.…”
Section: Introductionmentioning
confidence: 99%
“…As diferentes técnicas de conformação resultaram em diferenças microestruturais e de densificação. Os métodos de prensagem isostática e de colagem JESUS et al, 2016;RAFTERY et al, 2017;REN et al, 2018;CAMPOS et al, 2019;PRETTE;DICKEY, 2019;SCHWARZBACH et al, 2019;CAO;YOON et al, 2020).…”
Section: Conclusãounclassified